DETERMINATION OF ANTIOXIDANT ACTIVITY OF SALAK PONDOH (Salacca zalacca Gaertnes Voss) SKIN USING DPPH (2,2-diphenyl-1-picrylhydrazyl) METHOD AS ACTIVE INGREDIENT OF FACE MASK PRODUCT - Rusdi, Moh (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2024)
Based on the results of phytochemical tests, salak pondoh skin (Salacca zalacca Gaertnes Voss) contains alkaloid, flavonoid, and saponin compounds. Secondary metabolites such as alkaloids, flavonoids, and saponins show pharmacological effects as antioxidant compounds. Testing secondary metabolites in salak pondoh skin extract is the first step to using salak pondoh skin as an active component in face masks. This study aims to determine the antioxidant activity of salak pondoh skin extract using the DPPH (2,2-difenil-1-pikrilhidrazil)  method and its application as an active ingredient in face mask formulations. Antioxidant activity test of salak skin ethanol extract using DPPH method by determining IC50 value. From the test results, the IC50 antioxidant activity was 51.498 mg/L. This means that salak skin has strong antioxidant activity to capture free radicals